Research of descriptor based image normalization and comparative analysis of SURF, SIFT, BRISK, ORB, KAZE, AKAZE - Yakovleva, Olena Vladimirovna; Nikolaieva, Kateryna (Національний технічний університет "Харківський політехнічний інститут", 2020)
The subject of research is image normalization based on key points analysis. The purpose is development of mathematical models and their software implementation for normalization of image geometric transformations based on the analysis of SIFT, SURF, ORB, BRISK, KAZE, AKAZE descriptors; the model application for comparative analysis of descriptors based on expert assessments of normalization quality, time costs and other indicators; construction and usage in experiments the own dataset with 100 real image pairs which contains scenes of five types: buildings, plane images outside, plane images inside, natural and artificial textures; making conclusions about the performance of the considered descriptors to solve the normalization problem. Such methods are applied: SIFT, SURF, ORB, BRISK, KAZE, AKAZE descriptors for describing key points, the Nearest Neighbor Distance Ratio method or symmetric method for search of corresponding pairs of key points from different images, the RANSAC method for rejecting false correspondences and obtaining a homography matrix, similarity measures, software modeling. The results obtained: experimental normalization results by SIFT, SURF, ORB, BRISK, KAZE, AKAZE descriptors for 100 real pairs of own dataset (normalized images, their overlaps, quantitative descriptor evaluation, precision and recall estimation, time costs estimation, expert quality assessment, conversion of all indicator values to an 8-point rating scale); summary diagrams and conclusions about advantages and weaknesses of the compared descriptors; recommendations about the most-suitable-algorithm selection for solving normalization problem in specific cases.

Предметом досліджень є нормалізація зображень на основі аналізу характерних точок. Метою є розроблення математичних моделей та їх програмна реалізація для нормалізації геометричних перетворень зображень на основі аналізу дескрипторів SIFT, SURF, ORB, BRISK, KAZE, AKAZE; застосування цієї моделі для проведення порівняльного аналізу дескрипторів на основі експертних оцінок якості нормалізації, часових витрат та інших показників; формування та використання в експериментах власного датасету зі 100 реальних пар зображень, які містять сцени п’яти типів: будівлі та міські пейзажі, плоскі зображення, що зустрічаються на вулиці, плоскі зображення внутрішнього інтер’єру, природні та штучні текстури; висновки відносно використання розглянутих дескрипторів для вирішення задач нормалізації. Застосовуваними методами є: дескриптори SIFT, SURF, ORB, BRISK, KAZE, AKAZE для опису характерних точок, Nearest Neighbor Distance Ratio метод або симетричний метод для пошуку відповідних пар характерних точок з різних зображень, RANSAC метод для видалення хибних відповідностей та отримання параметрів матриці гомографії, міри подібності, програмне моделювання. Отримані результати: результати експериментів щодо нормалізації дескрипторами SIFT, SURF, ORB, BRISK, KAZE, AKAZE для 100 реальних пар зображень (нормалізовані зображення, їх перекриття, кількісні оцінкидескрипторів, precision and recall показники, часові витрати, експертні оцінки якості, конвертація всіх значень показників в 8-бальну рейтингову шкалу, підсумкові діаграми та висновки про переваги та слабкі місця дескрипторів, що порівнювалися; рекомендації відносно реалізації методу нормалізації у конкретних випадках.
Дослідження методу нормалізації зображень на базі дескрипторів та порівняльний аналіз дескрипторів SURF, SIFT, BRISK, ORB, KAZE, AKAZE
Keywords: normalization of geometric transformation; detector; нормалізація геометричних перетворень; детектор